Libraries Should Be Part of All This Book Talk - Dunn, Michael (Maine Policy Review, 2024)
Beneath the mass culture radar, book clubs, both online and in person, are on the rise, as is readership overall. Concurrently with these trends, a loneliness epidemic is emerging, presenting a promising opportunity for libraries to participate and facilitate a literary cultural moment. “Libraries Should Be Part of All This Book Talk” discusses the formation of Book Talk. To attract a wider readership and challenge any preconceived notions of a "book club," we intentionally present Book Talk as an "event" instead of a "club." The article highlights the enthusiasm that the events experienced, where attendees took part in animated conversations that far exceeded the proposed topics, with each event ending with eagerness for more. In an ever-changing world, libraries offer a trustworthy constant, even as they come under fire in the much-lauded “culture wars.” While libraries continue to adapt to the 21st century, they remain well placed in the popular consciousness as a place of community and heritage, which gives libraries the unique opportunity to hopefully grow this new literary cultural moment into our communities nation-wide.